Application of Confidence Intervals for Parameters of Nonparametric Spline Truncated Regression on Index Development Gender in East Java - Rifani Nur Sindy Setiawan; I Nyoman Budiantara; Vita Ratnasari (IPTEK Journal of Science, 2017)
The Gender Development Index (GDI) is an index that measures the achievement of human basic capability development for the health, education and economic sectors within a region by considering equality between men and women. In this research GDI with the factors that are suspected to affect it will be modeled using nonparametric spline truncated regression, because the results of scatterplot pattern of GDI with some predictor variables not to follow a certain pattern. Determination of predictor variables that significantly influence GDI by using confidence interval obtained high school enrollment rate of female population, morbidity of female population, percentage of last aid of birth by medical, and female labor-force participation rate have significantly influenced to GDI in East Java.